2022
DOI: 10.1038/s41467-022-33196-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon fertilization on naturally regenerated and planted US forests

Abstract: Over the last half century in the United States, the per-hectare volume of wood in trees has increased, but it is not clear whether this increase has been driven by forest management, forest recovery from past land uses, such as agriculture, or other environmental factors such as elevated carbon dioxide, nitrogen deposition, or climate change. This paper uses empirical analysis to estimate the effect of elevated carbon dioxide on aboveground wood volume in temperate forests of the United States. To accomplish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Thus, the estimates here represent projected changes in forest composition assuming those other factors are held constant or offset. Recent findings in Davis et al (2022) suggest many of the species here respond positively to CO 2 . However, no effects from CO 2 on tree growth have been reported in other studies (Gedalof & Berg, 2010;Girardin et al, 2016), suggesting there is still work to be done in this area.…”
Section: Uncertainties and Limitationsmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, the estimates here represent projected changes in forest composition assuming those other factors are held constant or offset. Recent findings in Davis et al (2022) suggest many of the species here respond positively to CO 2 . However, no effects from CO 2 on tree growth have been reported in other studies (Gedalof & Berg, 2010;Girardin et al, 2016), suggesting there is still work to be done in this area.…”
Section: Uncertainties and Limitationsmentioning
confidence: 68%
“…Importantly, our study does not account for the potential for elevated CO 2 to stimulate tree growth, improve water use efficiency, and potentially offset the decreases projected here (Chen et al, 2022;Davis et al, 2022;Song et al, 2019). However, it was not possible to incorporate the CO 2 fertilization directly in our analytical architecture given the spatial differences in CO 2 are small and the full panel of FIA plots has only been resampled in the past 20 years or so.…”
Section: Effects From Climate Changementioning
confidence: 99%
“…Our projected losses in forest and agricultural land could lower the supply for timber and agricultural products that could increase net returns to forest and agricultural land, which would, in turn, reduce the amount of land converted away from these uses. Of course, technological advances in crop yields (Hertel et al, 2016) or carbon fertilization in forests (Davis et al, 2022) could counter-act such supply reductions. A future research advance could integrate the land-use change model here with scenarios from structural market models of commodity prices under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Sohngen and Tian's (2016) numerical study finds that climate change will lower timber prices by a modest 15% relative to a nonclimate change baseline. Further, recent work has found that carbon fertilization has already increased timber productivity in at least some areas (Davis et al, 2022), which would also exert downward pressure on future timber prices and potentially counter any supply-induced price increases arising from land-use change out of forests. Other complications for projecting future commodity prices include global forces such as international trade policy and economic growth and land-use change in other countries.…”
Section: Landscape Simulationmentioning
confidence: 99%
See 1 more Smart Citation